32 Development of a triage tool including HE4, D-dimer, and fibrinogen for the assessment of women presenting with pelvic masses. (13th November 2020) - McKendry, K; Duff, S; O'Toole, S
Abstract : Introduction: 10% of pre- and 20% of post-menopausal women presenting with a pelvic mass will receive a diagnosis of ovarian cancer (OC). Algorithms are being formulated to improve on CA125 alone in classifying women presenting with pelvic masses as high or low risk for OC. The aim of this study was to evaluate novel biomarkers HE4, the Risk of Ovarian Malignancy Algorithm, the Risk of Malignancy Index I and II, D-dimer, and fibrinogen, alone or in combination, compared to CA125. Methods: Pre-operative serum samples were collected from 274 patients undergoing primary debulking surgery in an Irish tertiary referral centre. Logistic regression models and ROC curves were fitted for each biomarker alone and in combination. The partial area under the curve (pAUC) in the 90–100% specificity range was determined. Biomarker cutoffs were calculated at 90–100% and 98% specificity. Results: There were 89 pre- and 185 post-menopausal women, consisting of 144 benign, 41 borderline, and 89 OC cases. In the premenopausal group, no biomarker(s) outperformed CA125 (AUC 0.73; 95% CI 0.63–0.84). In the postmenopausal group, HE4 + D-dimer + fibrinogen outperformed CA125 alone (AUC 0.83 versus 0.77, p= 0.023). HE4 + D-dimer had the highest pAUC at 72.59 (95% CI 66.16–79.72) and outperformed CA125 (p = 0.001). Conclusion: The addition of biomarker(s) to CA125 does not increase OC detection in premenopausal women. A novel biomarker panel (HE4 + D-dimer + fibrinogen) improved the diagnostic accuracy of CA125 alone in postmenopausal women and could aid in the preoperative triaging of pelvic masses.